A Descriptive Study of the Relationship Between Learning Motivation and Fiqh Performance at MI Darul Quran - Ananda Rizki, Reffy; Qalbia, Farhah; Kharis Kurniawan, Akhmad; Ropitasari, Anna; ulfah, Nadra (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2025)
Fiqh, as a core subject in Islamic education within Indonesian madrasahs, plays a vital role in shaping students’ moral reasoning and Islamic character. However, academic outcomes in this subject often do not meet expected standards, with learning motivation frequently identified as a major contributing factor. This study explores the relationship between students’ learning motivation and their academic performance in Fiqh at MI Darul Quran, Sawangan, Depok. Utilizing a quantitative descriptive approach, the research analyzed responses from 93 sixth-grade students through separate instruments: a Likert-scale motivation questionnaire and end-of-semester Fiqh scores. The findings reveal that while 92% of students exhibited high levels of learning motivation—particularly intrinsic motivation—only 18.27% achieved high academic performance in Fiqh. This disparity suggests that motivation alone is insufficient for academic success and highlights the importance of integrating effective pedagogical strategies, teacher involvement, family support, and contextual learning environments. The study underscores the need for holistic instructional models that bridge motivation with cognitive outcomes, offering practical implications for improving Islamic education in primary-level madrasahs. Future research is recommended to employ paired-data designs to better understand the causal relationship between motivational and academic variables.